Dual-Band 8x8 Adaptive Array Antenna for 3.5/5 GHz - Kale S. R (Journal of Electronic Design Engineering, 2017)
This paper gives result analysis for the adaptive antenna array is expected to meet data rate requirement for 4G communication for Direct Sequence CDMA (DS-CDMA) antenna application.In this paper 4G smart planner dual band phase array suitable Long Term Evolution (LTE) at 3.5 GHz for fourth generation (4G)and also Wireless Local Area Network(WLAN) at 5GHz system isdeveloped. The proposed planar array antenna is build using micro strip U slotted patch antenna element. Separate feeding techniques are used for every element of the smart planar array antenna and elevation direction at Sixty degree phase shift absent of any grating lobes. At Sixty degree phase shift, the gain is to be 22.62dB without changing in the mutual coupling. In this single element and linear sub arrays with 1x2 and 1x4 dimension of this element are designed.